Des savoirs locaux insaisissables ? L’exemple de la tenderie aux grives en Ardenne - Agnès Fortier (VertigO, 2005)
Local knowledges are now considered as legitimate in the management of nature. They are mobilised in the same way as scientifical and technical knowledge to contribute to the elaboration of standards compatible with the conservation of biodiversity in participatory approach schemes. However, this integration of lay knowledge is not easy. The deep study of trap activity, thrush snaring, based on participative observation, reveals the difficulties to access and to highlight these knowledges. It supposes for the investigator to make a detour by learning which is a necessary precondition to account for the nature and the characteristics of these knowledges, because one of their particularities is that they are rarely specified. The unformulated mode of expression of theses know-how combined with the secret of the activity, doesn’t facilitate exchange, communication and transmission of these knowledges.